2015
DOI: 10.1177/2158244015621776
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in Rural Caregivers of Persons With Dementia

Abstract: Informal caregiving for dementia is common and often affects caregiver mental health. In addition to typical stressors faced by caregivers of persons with dementia (PWDs), rural caregivers often face additional stressors associated with living in more remote locations; unfortunately, this group is largely understudied. Ninety-three caregiver-PWD dyads completed measures of social support, perceived control, self-efficacy, burden, and cognitive functioning. Measures of PWD activities of daily living and mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Li et al (2012) suggest that to meet the needs of people with dementia in rural places, it is important to address the psychological and social needs of the carer, particularly to reduce levels of carer burden. Concordantly, others also recommend that services should work to support carers to reduce levels of burden (Heggie et al, 2012;Werntz et al, 2015;Ainamani et al, 2020).…”
Section: Improving the Experience Of Dementia In Rural Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2012) suggest that to meet the needs of people with dementia in rural places, it is important to address the psychological and social needs of the carer, particularly to reduce levels of carer burden. Concordantly, others also recommend that services should work to support carers to reduce levels of burden (Heggie et al, 2012;Werntz et al, 2015;Ainamani et al, 2020).…”
Section: Improving the Experience Of Dementia In Rural Areasmentioning
confidence: 99%
“…Furthermore, educating people with a recent diagnosis of dementia about the services and supports that are available to them will assist them to make their own decisions about their future (Di Gregorio et al, 2015). Carers have also recommended that education, training and courses be made available to them, to help them prepare and to enhance their skills in providing the best care possible (Alzheimer's Australia, 2007;Saunders, 2013;Innes et al, 2014;Alzheimer's Society, 2017;Bauer et al, 2019;Gibson et al, 2019), and researchers have made similar recommendations for supporting carers (Werntz et al, 2015;Cox et al, 2019;Krutter et al, 2020). A recent study of carers of people with dementia in rural Kentucky revealed gaps in information needs identified during a question-and-answer session, including risk factors, behaviour management, diagnosis and medication (Bardach et al, 2021).…”
Section: Improving Education and Awareness For Professionals And The ...mentioning
confidence: 99%
“…Thus, carers may often become proxy evaluators of patient’s needs and health status. Under different disease conditions (Kozlowski et al, 2015; Moyle et al, 2012; Werntz et al, 2015), quality of life is perceived in a different manner by patients and caregivers: there is high agreement on the global quality of life and physical functioning perception by patients and caregivers, but low agreement for psychosocial aspects related to the patient’s condition. Proxy-related information does not always positively correlate with the patient’s condition, though, and caregivers tend to underestimate patient’s health status (Bravo et al, 2017; Libert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Caring for patients with dementia has significant effects on the caregiver's mental health. Approximately 65% of all older adults in the United States receiving informal care had some form of dementia, 25 while that number increases to 75% of all informal care provided in rural areas 26 . Informal caregivers of persons with dementia are more prone to developing clinical depression and anxiety, reporting changes in mental processing speed, decreased immunity, requiring more sick days, and reporting familial conflict and caregiver strain 26 .…”
mentioning
confidence: 99%